Ciprofloxacin induced fixed drug eruption - Ravishankar, M.; Deepika, G.; Shwetha, S. (International Journal of Basic & Clinical Pharmacology, 2017)
Fixed drug eruption (FDE) is a clinical entity occurring in the same site or sites each time the drug is administered. Acute lesions appear as sharply marginated erythematous plaques, which are usually found on lips, genitalia, abdomen, and legs. The eruptions usually occur within hours of administration of the offending agent and resolves spontaneously without scarring after few weeks of onset. Most common drugs causing FDE are sulfonamides, tetracyclines, salicylates, barbiturates, doxycycline, fluconazole, clarithromycin, etc. Ciprofloxacin, a widely used fluoroquinolone antimicrobial, induces cutaneous adverse drug reactions (ADRs) in about 1-2% of treated patients. Urticaria, angioedema, maculopapular exanthems, and photosensitivity are the most frequently documented cutaneous adverse reactions. In this case report, the patient soon after taking ciprofloxacin tablets, developed itching in the lips, palms and in scrotal region. On continuing the treatment, the next day he developed fluid filled lesions over palm, knuckle, and hyperpigmentation. He gives a history of severe itching and rashes in scrotal region. He gives a history of similar complaints in the previous month after taking ciprofloxacin medication. There was no history of intake of any other medication. On examination, bullous lesions and pustules in finger webs, hyperpigmentation on knuckles, and scrotal erosions were seen. In the present case report, the patient presented with FDE immediately after oral administration of ciprofloxacin and got completely cured after stopping the drug and taking adequate treatment. According to the Naranjo’s ADR probability scale (score=8), this ADR is categorized as a “probable” reaction to the drug.